(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Recurrent abortion is a worldwide problem, with undefined causes. Apoptosis could play a major role in the process. Objective: Detect the expression of Bcl-2 protein at the materno-fetal interface in patients with recurrent pregnancy loss (RPL). Methods: Immunohistochemistry analysis of Bcl-2 protein using paraffin embedded sections of curate samples obtained from 40 women divided into three groups: 24 women with recurrent abortion, 10 women with abortion for the first time, and 6 women with induced abortion. Results: The mean value of the expression of Bcl-2 protein was (57.9± 1.4), which is significantly higher than that of the second group (39± 1.9), and the third group (47.5± 2.4). Conclusion: High expression of Bcl-2 protein in women with recurrent abortion may have a protective role in preventing placental apoptosis that leads to failure of pregnancy. Keywords: Bcl-2, recurrent pregnancy loss (RPL).